The Level of Knowledge of kindergarten Teachers in Detecting Congnitive Difficulties among Kindergarten Children - A Field Study in Lattakia City - كيخي, اريج; ربا حيدر, (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The research aimed to identify the degree of knowledge of kindergarten teachers in diagnosing cognitive difficulties among kindergarten children in the city of Latakia, and to identify the differences between the averages of the answers of the research sample members (kindergarten teachers) to the research questionnaire according to the research variables (training courses, scientific and educational qualification, years of experience) . The research was applied to (156) female teachers working in (16) private kindergartens in the city of Latakia. A questionnaire was used to ask the teachers about the degree of knowledge of kindergarten teachers in diagnosing cognitive difficulties. , and using the descriptive approach. The results of the research showed that The degree of knowledge of kindergarten teachers in diagnosing cognitive difficulties was high, and there were no differences in the degree of knowledge of kindergarten teachers in diagnosing cognitive difficulties according to the variable years of experience, and there were differences in the degree of knowledge of kindergarten teachers in diagnosing cognitive difficulties according to Variables (training courses: in favor of teachers who underwent training courses, and scientific and educational qualification in favor of a degree in education).